Ultrastructural analysis of the effect of mating delay on cell death in the ovaries of virgin honey bee (Apis mellifera L.) queens - Berger, Bruno [UNESP]; da Cruz-Landim, Carminda [UNESP] (Int Bee Research Assoc, 2009)
This paper reports the effect of mating delay on the ovaries of virgin Apis mellifera queens using analysis by light and electron microscopy. The results showed that the terminal filament did not change throughout the study period, but its length decreased and germarium size increased with age of queens. Cell death events were observed in the ovaries from emergence but not in the terminal filament. Isolated cell death occurs in young queens prior to mating age, but cell death substantially increases if mating does not occur in the normal period. Two morphological types of cell death were observed: apoptosis-like death in germ line cells and autophagic-like death in somatic line cells. Cell death in germ line cells is apparently more frequent in cystocytes. Death after oocyte differentiation seems only to affect future nurse cells.
Keywords: apoptosis; authophagy; honey bee queen; morphology; Apis mellifera